Rituximab inhibits structural joint damage in patients with rheumatoid arthritis with an inadequate response to tumour necrosis factor inhibitor therapies. Issue 2 (3rd April 2008) - Keystone, E; Emery, P; Peterfy, C G; Tak, P P; Cohen, S; Genovese, M C; Dougados, M; Burmester, G R; Greenwald, M; Kvien, T K; Williams, S; Hagerty, D; et al.
Abstract : Objective: To determine if treatment with a B cell-targeted therapy can inhibit the progression of structural joint damage in patients with rheumatoid arthritis (RA), exhibiting an inadequate response to tumour necrosis factor (TNF) inhibitors. Methods: In this phase III study, patients with an inadequate response to a TNF inhibitor and receiving methotrexate were randomised to rituximab or placebo. Radiographs were obtained at baseline, week 24 and week 56 after randomisation. Patients with an inadequate response to their randomised therapy could receive rescue medication from week 16. From week 24, eligible patients from both treatment arms could receive open-label rituximab. Patients were analysed according to their original treatment group. Radiographs were scored using the Genant-modified Sharp method. The primary radiographic endpoint was change in total Genant-modified Sharp score at week 56. Results: Rituximab treatment caused significant reduction in joint damage progression compared with placebo. The mean change from baseline in the total Genant-modified Sharp score at week 56 was significantly lower for patients treated with rituximab than for patients treated with placebo (1.00 vs 2.31; p = 0.005), and was supported by changes in erosion score (0.59 and 1.32 for rituximab plus methotrexate vs placebo plus methotrexate, respectively; p = 0.011) and joint space narrowing score (0.41 and 0.99, respectively; p< 0.001). Conclusions: This study provides the first evidence that a B cell-targeted therapy—rituximab—can significantly inhibit the progression of structural joint damage in patients with RA with long-standing, active and treatment-resistant disease.